Relating the strength of graphene/metal composites to the graphene orientation and position. (May 2020) - Shuang, Fei; Aifantis, Katerina E.
Abstract: This letter presents new insight on the underlying strengthening mechanisms that take place during deformation of iron-graphene (Fe/Gr) composites. Molecular dynamics revealed that the Gr orientation dictated the dislocation evolution during compression, revealing three possible dislocation-Gr interaction mechanisms: transmission, reflection and gliding. A new numerical materials design was therefore proposed of a lamellae Fe-Gr structure with a short graphene sheet inserted in Fe, whose orientation resulted in reflection. Decreasing the distance between the long and short Gr-sheets resulted in the stronger composites. This method can be used for predicting the properties of graphene reinforced composites based on the Gr structure. Graphical abstract: Image, graphical abstract